2001
DOI: 10.1046/j.0022-0477.2001.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Change of fire frequency in the eastern Canadian boreal forests during the Holocene: does vegetation composition or climate trigger the fire regime?

Abstract: Summary1 Studies on the variability of natural fire regimes are needed to understand plant responses in a changing environment. Since vegetation changes might follow or trigger changes in fire frequency, climate models suggest that changes in water balance will accompany current global warming, and the response of fire regimes to Holocene hydro-climate changes and vegetation switches may thus serve as a useful analogue for current change. 2 We present high-resolution charcoal records from laminated cores from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 39 publications
7
154
1
6
Order By: Relevance
“…in Yellowstone (Meyer et al 1995;Millspaugh et al 2000), Idaho (Meyer et al 2001), Oregon (Long et al 1998), southwestern BC (Gavin et al 2003b;Hallett et al 2003a;Lertzman et al 2002), and southeastern BC (Hallett and Walker 2000;Hallett et al 2003b). This signal appears less marked in the tropics (Horn and Sanford 1992;Turcq et al 1998) and in other mid-latitude regimes, such as in eastern Canada (Carcaillet et al 2001) and New Zealand (Molloy et al 1963). Cumming et al (2002) reported on persistent millennial-scale effects on moisture availability recorded at Big Lake, BC, in the semi-arid Cariboo region, some 500 km south of the Bear Lake site.…”
Section: Discussionmentioning
confidence: 99%
“…in Yellowstone (Meyer et al 1995;Millspaugh et al 2000), Idaho (Meyer et al 2001), Oregon (Long et al 1998), southwestern BC (Gavin et al 2003b;Hallett et al 2003a;Lertzman et al 2002), and southeastern BC (Hallett and Walker 2000;Hallett et al 2003b). This signal appears less marked in the tropics (Horn and Sanford 1992;Turcq et al 1998) and in other mid-latitude regimes, such as in eastern Canada (Carcaillet et al 2001) and New Zealand (Molloy et al 1963). Cumming et al (2002) reported on persistent millennial-scale effects on moisture availability recorded at Big Lake, BC, in the semi-arid Cariboo region, some 500 km south of the Bear Lake site.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism was proposed to have worked in periods as recent as the large fire years of the 1950s (Sirois & Payette 1991). In a study of pollen and charcoal analysis in Québec, Carcaillet et al (2001) found that thermal optima in the region were associated with moist climate and reduced fires, whereas colder conditions brought abundant northwestern dry air masses that favoured shorter fire cycles. Under such conditions, they proposed that an eventual global warming would probably be associated with increased moisture in the area and, thus, with a less severe fire regime.…”
Section: Climate and Wildfires In North America M Macias Fauria And Ementioning
confidence: 99%
“…Based on this, general circulation models have been used to predict increases in area burned of up to 118% from the present in doubled and tripled CO 2 scenarios by the end of the twenty-first century (Gillett et al 2004;Flannigan et al 2005). Overall, the area burned in Canada is predicted to increase due to an increase in temperature, despite regional differences-for example predicted decreases in area burned for the eastern North American boreal forests ( Flannigan et al 1998;Carcaillet et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These differences may have resulted from the regional climatic setting. However, we have to take in account the relative sensibility of the different proxies and/or seasonality of climate (Carcaillet et al, 2001b;Wick et al, 2003;Magny et al, 2007). Actually, the fire-frequency and lake-level records are more sensitive to summer conditions (Magny, 1998).…”
Section: Early Holocene Fire Regime and Climate Seasonalitymentioning
confidence: 99%